Fostering trust, collaboration, and a culture of continuous quality improvement: A call for transparency in medical school accreditation - Javidan, Arshia; Raveendran, Lucshman; Rai, Yeshith; Tackett, Sean; Kulasegaram, Kulamakan Mahan; Whitehead, Cynthia; Rosenfield, Jay; Houston, Patricia (Canadian Medical Education Journal, 2020)
Medical schools provide the foundation for a physician’s growth and lifelong learning. They also require a large share of government resources. As such, they should seek opportunities to maintain trust from the public, their students, faculty, universities, regulatory colleges, and each other. The accreditation of medical schools attempts to assure stakeholders that the educational process conforms to appropriate standards and thus can be trusted. However, accreditation processes are poorly understood and the basis for accrediting authorities’ decisions are often opaque. We propose that increasing transparency in accreditation could enhance trust in the institutions that produce society’s physicians. While public reporting of accreditation results has been established in other jurisdictions, such as Australia and the United Kingdom, North American accrediting bodies have not yet embraced this more transparent approach. Public reporting can enhance public trust and engagement, hold medical schools accountable for continuous quality improvement, and can catalyze a culture of collaboration within the broader medical education ecosystem. Inviting patients and the public to peer into one of the most formative and fundamental parts of their physicians’ professional training is a powerful tool for stakeholder and public engagement that the North American medical education community at large has yet to use.